2015
DOI: 10.1002/chem.201501260
|View full text |Cite
|
Sign up to set email alerts
|

Walking Down the Chalcogenic Group of the Periodic Table: From Singlet to Triplet Organic Emitters

Abstract: The synthesis, X-ray crystal structures, ground- and excited-state UV/Vis absorption spectra, and luminescence properties of chalcogen-doped organic emitters equipped on both extremities with benzoxa-, benzothia-, benzoselena- and benzotellurazole (1X and 2X ) moieties have been reported for the first time. The insertion of the four different chalcogen atoms within the same molecular skeleton enables the investigation of only the chalcogenic effect on the organisation and photophysical properties of the materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 85 publications
5
82
0
1
Order By: Relevance
“…31 Furthermore, a clear heavy-atom effect was shown recently for two families of organic bis-benzoazole luminophores doped with oxygen, sulfur, selenium, or tellurium. 32 We have detected significantly higher luminescence intensities for selenophene-containing ARC-Lum probes in complex with a …”
Section: ■ Results and Discussionmentioning
confidence: 76%
“…31 Furthermore, a clear heavy-atom effect was shown recently for two families of organic bis-benzoazole luminophores doped with oxygen, sulfur, selenium, or tellurium. 32 We have detected significantly higher luminescence intensities for selenophene-containing ARC-Lum probes in complex with a …”
Section: ■ Results and Discussionmentioning
confidence: 76%
“…This suggests that once a pyrid‐4‐yl moiety contacts a DITFB, it seemingly depletes the Se‐CGP moiety, raising the strength of the double EBIs. This observation is in accordance with previous results, for which CF 3 ‐bearing Se‐CGP derivatives form doubly EB‐bonded dimers …”
Section: Resultsmentioning
confidence: 99%
“…X‐ray diffraction clearly showed that the steric hindrance between the TfO substituents at the central bay position of the quaterrylene board triggers a strong deformation of the central perylene planarity, twisting the naphthyl portions of each perylene units. Remarkably, this unique core‐twisted quaterrylene was found to emit in the NIR spectral region, with a phosporescence maximum centered at 1716 nm at 77 K. Considering that, up to now, the library of NIR‐emissive organic materials that emit beyond 750 nm is truly limited and it is mostly based on metal complexes and chalcogen‐containing hybrids, [ ][ ] this finding is very promising in the design of efficient organic NIR‐emitting materials. Moreover, third‐order NLO measurements on solutions and thin film containing the relevant dye showed considerably high NLO second hyperpolarizability values (15.7 ± 0.2 × 10 −31 esu) in comparison with those reported in the literature for parent π ‐extended PAHs.…”
Section: Resultsmentioning
confidence: 99%